Analysis of The Effectiveness Level of Trans Sarbagita Bus as Public Transport in Denpasar City - Ni Kadek Della; Anak Agung Istri Ngurah Marhaeni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Public transportation is a primary necessity for supporting daily activities in Denpasar City. One mode of transport that plays a strategic role is the Trans Sarbagita Bus. As a mass transportation service, this bus system is expected to provide effective, efficient, and affordable mobility. This study aims to analyze: (1) public perception of the effectiveness of the Trans Sarbagita Bus service; (2) the simultaneous effect of accessibility, punctuality, and ticket price on service effectiveness; (3) the partial effect of each of these variables; and (4) the strengths, weaknesses, opportunities, and threats (SWOT) of the Trans Sarbagita Bus system. A quantitative method with an associative approach was employed. Data were collected from 105 active respondents through observation, interviews, and a five-point Likert scale questionnaire, and analyzed using multiple linear regression via SPSS. The findings show that: (1) public perception is generally positive, especially in terms of comfort and safety, although accessibility and punctuality remain suboptimal; (2) accessibility, punctuality, and ticket price simultaneously have a significant effect on service effectiveness; (3) each of these variables also has a positive and significant partial effect; and (4) strengths lie in low fares and safety, while key weaknesses include limited access and delays. Opportunities stem from policy support and rising public awareness, whereas threats include the dominance of private vehicles and low intermodal integration. It is recommended that the government enhance public transport campaigns through media and community partnerships, as well as expand bus stop access and intermodal connectivity to improve service effectiveness.